Prevalence of Coracoclavicular Joint in Patients Visiting Radio-Diagnosis Department at College of Medical Sciences, Chitwan - Pandit, Ruku; Shrestha, Sunara; Sharma, Nitasha (Journal of Chitwan Medical College, 2019)
Introduction: Coracoclavicular joint (CCJ) is a true synovial joint between superior surface of coracoid process of scapula and conoid tubercle of clavicle. The radiological prevalence of CCJ in various population ranges 0.55% to 21%. The CCJ are mostly discovered incidentally and is rarely associated with any symptom. Sometimes it may present with shoulder pain, limitation of shoulder movement, upper limb paresthesia and osteoarthritis of itself or adjacent acromioclavicular joint. Hence, this study is aiming to determine the prevalence of anomalous CCJ in patient visiting department of Radio-diagnosis in College of Medical Sciences, Bharatpur, Chitwan, Nepal and to observe association of CCJ with laterality, sides and gender. Methods: A total of 1936 digital chest x-rays films were observed for the presence of CCJ, out of which 1097 images were of male and 839 of females. Age of study population ranged from 3 to 90 years. The data obtained were analyzed using Stastical Package for Social Science version (SPSS) 16.0. The prevalence of CCJ was calculated. The cases with CCJ were further analyzed to evaluate the association of CCJ with laterality, sidedness and gender using Chi-square for one-dimensional “goodness of fit” test. Chi-square of Independence was employed to compare the various parameters (laterality and side) with genders. Results: The prevalence of CCJ was 4.6%. CCJ was more frequently observed in male (67.42%) than female (32.57%). Unilateral occurrence of CCJ (55.06%) was slightly more than bilateral (44.94%). Gender difference was not significantly associated with laterality and sidedness of joint (p<0.05). The incidence of CCJ was more in second decade of life in both male and female. Conclusion: CCJ is not rare, hence, knowledge of presence of CCJ as an etiology of shoulder pain is essential for rational therapy and will prevent misdiagnosis.